Clinical height measurements are unreliable: a call for improvement. Issue 10 (October 2016) - Mikula, A.; Hetzel, S.; Binkley, N.; Anderson, P.
Abstract Summary Height measurements are currently used to guide imaging decisions that assist in osteoporosis care, but their clinical reliability is largely unknown. We found both clinical height measurements and electronic health record height data to be unreliable. Improvement in height measurement is needed to improve osteoporosis care. Introduction The aim of this study is to assess the accuracy and reliability of clinical height measurement in a university healthcare clinical setting. Methods Electronic health record (EHR) review, direct measurement of clinical stadiometer accuracy, and observation of staff height measurement technique at outpatient facilities of the University of Wisconsin Hospital and Clinics. We examined 32 clinical stadiometers for reliability and observed 34 clinic staff perform height measurements at 12 outpatient primary care and specialty clinics. An EHR search identified 4711 men and women age 43 to 89 with no known metabolic bone disease who had more than one height measurement over 3 months. The short study period and exclusion were selected to evaluate change in recorded height not due to pathologic processes. Results Mean EHR recorded height change (first to last measurement) was −0.02 cm (SD 1.88 cm). Eighteen percent of patients had height measurement differences noted in the EHR of ≥2 cm over 3 months. The technical error of measurement (TEM) was 1.77 cm with a relative TEM of 1.04 %. None of the staff observed performing height measurements followed all recommended height measurement guidelines. Fifty percent of clinic staff reported they on occasion enter patient reported height into the EHR rather than performing a measurement. When performing direct measurements on stadiometers, the mean difference from a gold standard length was 0.24 cm (SD 0.80). Nine percent of stadiometers examined had an error of >1.5 cm. Conclusions Clinical height measurements and EHR recorded height results are unreliable. Improvement in this measure is needed as an adjunct to improve osteoporosis care.